Indeks glikemik dan beban glikemik bolu kukus dan cookies labu kuning (Cucurbita moschata Durch) berbahan formula modisco: Indeks Glikemik dan Beban Glikemik Bolu Kukus dan Kukis Labu Kuning (Cucurbita moschata Durch) Berbahan Formula Modisco - Sugeng Maryanto; Windy Harly; Dian Oktianti (Amerta Nutrition, 2022)
Background: Modisco (modified dried milk and coconut oil) is a processed food in liquid form that contains high energy and protein. Provision of high-calorie, high-protein supplementary food is necessary for nutritionally vulnerable age groups who have problems with digestion. The development of the modisco formulation made from pumpkin into processed steamed cakes and cookies based on the modisco formulation aims to improve taste and increase the length of time of storage before consumption. The addition of pumpkin as a source of fiber in processed steamed cakes and cookies is a choice of low glycemic index and glycemic load snacks. Objectives: This study conducted to describe the glycemic index and glycemic load of processed steamed cakes and cookies using the ingredients of the modified pumpkin (Cucurbita moschata Durch) formulation. Methods: The design of this study was an experimental in vitro vivo design. The in vitro study was carried out by making steamed cakes and cookies with the main ingredients of the modisco III formula with several formulations, then the best formula was selected to be given as an in vivo treatment. The respondent in this study were 10 Ngudi Waluyo students aged 17-25 years, who had a normal Body Mass Index (18.5 to 22.9 kg/m2), normal pre-prandial blood sugar (70-100 mg/dl), and never suffered from diabetes mellitus. The respondents were previously  fast at night for 10 hours at least, and do not strenuous activities during preparation for blood collection. The first blood collection was taken at 0 minutes, carried out at 7 am through the fingertips (peripheral blood) carried out by the nurse, then the respondents were given steamed cakes to one group and cookies to the other group, each of 50 grams. Blood collection was continued at 30, 60, 90, and 120 minutes. Blood sugar levels were measured using a gluco-test. The blood glucose data obtained was then analyzed to determine the glycemic index and glycemic load of processed steamed cakes and cookies.. Results: The value of glycemic index and glycemic load of processed steamed cake products were 23.00% and 5.75, respectively, while those of the cookie product were 38.9% and 9.75, respectively. Conclusions: The value of the glycemic index and glycemic load of processed products of steamed cake and yellow pumpkin pumpkin cookies formula are in the low category.